Smoking-related gut microbiota alteration is associated with obesity and obesity-related diseases: results from two cohorts with sibling comparison analyses - Yiting Duan; Chengquan Xu; Wenjie Wang; Xiaoyan Wang; Nuo Xu; Jieming Zhong; Weiwei Gong; Weifang Zheng; Yi-Hsuan Wu; April Myers; Lisa Chu; Ying Lu; et al. (BMC Medicine)
Abstract Background Individuals who smoke tend to have a lower body mass index (BMI) but face an increased risk of obesity-related diseases. This study investigates this paradox from the perspective of gut microbiota. Methods We conducted microbiome analyses to identify smoking-related microbial genera and created a smoking-related microbiota index (SMI) using 16S rRNA sequencing data from 4000 male participants in WELL-China cohort and Lanxi cohort. We employed logistic regression to explore the association between SMI and obesity indices derived from dual-energy X-ray absorptiometry. Cox regression analyses were conducted to explore the association of SMI with incident of obesity-related diseases. To further control for unmeasured familial confounders, sibling comparison analyses were conducted using between-within (BW) model. Results The smoking-related microbiota index (SMI) showed a positive association with BMI and other obesity indices. Further analyses revealed that SMI is linked to obesity-related diseases, with hazard ratios (95% confidence intervals) of 1.97 (1.41–2.75) for incident diabetes, 1.31 (1.01–1.71) for major adverse cardiovascular events, and 1.70 (1.05–2.75) for obesity-related cancers. Results from sibling comparison analyses reinforced these findings. Conclusions While smoking may reduce weight through various mechanisms, alterations in gut microbiota related to smoking are associated with weight gain. Further research is required to determine if changes in the smoking-related microbiome contribute to weight gain following smoking cessation.